(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2019)
تم توضيح طريقة ناجحة لإكثار البنفسج الأفريقيAfrican Violet (Santpaulia ionantha.L.) باستخدام تقنيات زراعة الأنسجة النباتية. فتبين، بعد زراعة قطع صغيرة من النبات في وسط موراشيج وسكوغ مضافاُ إليه أحد منظمات النمو المعروفة أو مزيجاُ منها وبتراكيز متنوعة، أن الوسط MS2 (MS+4.44µM BA+1.47µM IBA +0.58µM GA3)، هو الأفضل في تحريض إنتاج نموات خضرية جديدة. وقد تم تجذير هذه النموات بنسبة 95% باعادة زراعتها على وسطي تجذير أحدهما سائل والآخر يحتوي أجار متصلب هما: MR1 (أجار MS+4.91µM IBA+0.58µM GA3+ ( و MR2 (بيتموس (MS+4.91µM IBA+0.58µM GA3+. ثم نقلت النموات المجذرة إلى أصص وتمت أقلمتها تدريجياً مع الوسط الخارجي وبنسبة نجاح 85%. A successful and detailed In vitro propagation system for rapid micropropagation of the African Violet (Santpaulia ionantha.L.) has been developed. After planting in vitro culture of explants onto MS basal medium with a combination of growth regulators at different concentrations, it turns out that MS2, which is supplemented with 4.44µM BA+1.47µM IBA+0.58µM GA3, is the best in inducing the production of new shoots. Shoots are rooted with efficiency of 95% by transferring them to two agar-gelled or liquid media with peatmoss substrate (MR1 and MR2) containing MS basal media supplemented with 4.9µM IBA. Rooted plantlets are transplanted into pots and gradually acclimatized to natural conditions with 85 % efficiency.